Occurrence of mycotoxins in pulses. Issue 5 (25th July 2022) - Acuña‐Gutiérrez, Catalina; Jiménez, Víctor M.; Müller, Joachim
Abstract : Abstract: Pulses, dry grains of the Fabaceae family used for food and feed, are particularly important agricultural products with increasing commercial and nutritional relevance. Similar to other plant commodities, pulses can be affected by fungi in the field and during postharvest. Some of these fungi produce mycotoxins, which can seriously threaten human and animal health by causing acute poisoning and chronic effects. In this review, information referring to the analysis and occurrence of these compounds in pulses is summarized. An overview of the aims pursued, and of the methodologies employed for mycotoxin analysis in the different reports is presented, followed by a comprehensive review of relevant articles on mycotoxins in pulses, categorized according to the geographical region, among other considerations. Moreover, special attention was given to the effect of climatic conditions on microorganism infestation and mycotoxin accumulation. Furthermore, the limited literature available was considered to look for possible correlations between the degree of fungal infection and the mycotoxin incidence in pulses. In addition, the potential effect of certain phenolic compounds on reducing fungi infestation and mycotoxin accumulation was reviewed with examples on beans. Emphasis was also given to a specific group of mycotoxins, the phomopsins, that mainly impact lupin. Finally, the negative consequences of mycotoxin accumulation on the physiology and development of contaminated seeds and seedlings are presented, focusing on the few reports available on pulses. Given the agricultural and nutritional potential that pulses offer for human well‐being, their promotion should be accompanied by attention to food safety issues, and mycotoxins might be among the most serious threats. Practical Application : According to the manuscript template available in the website, this section is for "JFS original research manuscripts ONLY; optional". Since we are publishing in CRFSFS this requirement will not be done.